HUBUNGAN ANTARA KADAR GLUKOSA SERUM DENGAN JUMLAH TROMBOSIT PADA PENDERITA DIABETES MELITUS TIPE 2 DI RS PKU MUHAMMADIYAH YOGYAKARTA - Atik Diyah Megasari (FKU 12 UMY, 2012)

(untitled)
Background: In type 2 Diabetes Mellitus patient, hyperglycemia can be happened and cause oxidative stress, protein kinase c activation, nitric oxide and prostasiklin reduction. It can cause platelet dysfunction that influence the platelet count and cause trombocytopenia. Research Objective: To know the relation between glucose levels with platelet count in type 2 Diabetes Mellitus patient in PKU Muhammadiyah Yogyakarta Hospital. Method design: This research related between glucose levels with